Объяснение:
Для решения примера нам понадобится формула куба суммы:
(a + b)^3 = a^3 + 3 * a^2 * b + 3 * a * b^2 + b^3.
(0,2m + 0,1n)^3 = (0,2m)^3 + 3 * (0,2m)^2 * (0,1n) + 3 * 0,2m * (0,1n)^2 + (0,1n)^3 = 0,008m^3 + 0,012m^2n + 0,006mn^2 + 0,001n^3.
ответ: 0,008m^3 + 0,012m^2n + 0,006mn^2 + 0,001n^3.
Объяснение:
Для решения примера нам понадобится формула куба суммы:
(a + b)^3 = a^3 + 3 * a^2 * b + 3 * a * b^2 + b^3.
(0,2m + 0,1n)^3 = (0,2m)^3 + 3 * (0,2m)^2 * (0,1n) + 3 * 0,2m * (0,1n)^2 + (0,1n)^3 = 0,008m^3 + 0,012m^2n + 0,006mn^2 + 0,001n^3.
ответ: 0,008m^3 + 0,012m^2n + 0,006mn^2 + 0,001n^3.